Impacts of Stefan Blowing on Thermophoretic Particle Deposition in Sisko Nanofluid Flow Over a Riga Plate with Soret and Dufour Effects - Abbas, Munawar; Khan, Nargis; Hashmi, M. S.; Rezapour, Shahram; Ullah, Hameed; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2024)
The proposed framework considers the thermosolutal Marangoni convective flow of Sisko (MOS2-CH3OH) nanofluid over a Riga surface with the effects of Stefan blowing and thermophoretic particle deposition. The phenomena of mass and heat are discussed in relation to Soret and Dufour impacts. Electrodes and magnets are arranged on a plate to make up the Riga plate. Since the fluid conducts electricity, the Lorentz force upsurges exponentially in the vertical direction. There are numerous possible uses for this study in different disciplines. The design and production of thin films, coatings, and nanostructured materials can be enhanced by knowledge of how nanoparticles settle onto surfaces under various fluid flow conditions. By optimizing fluid flow and particle deposition processes, engineering insights from this work can guide the development of more efficient heat transfer systems, such as heat exchangers and cooling technologies. The nonlinear governing PDEs are converted into nonlinear ODEs using appropriate transformations. The resultant system of highly nonlinear equations can be solved analytically by using the homotopy analysis method (HAM). The significance of factors on the flow, thermal, and concentration fields are thoroughly explained with the use of tables and figures. Higher Marangoni convection parameter in more effective heat and mass transport within the liquid as well as higher induced flows when the Marangoni convection parameter is increased. A more uniform distribution of these properties throughout the liquid is the result of decreasing temperature and concentration profiles.
Keywords: Sisko nanofluid; thermophoretic particle deposition; Soret-Dufour effects; Marangoni convection; Stefan blowing impact